2013
DOI: 10.1136/bcr-2013-009546
|View full text |Cite
|
Sign up to set email alerts
|

An unusual cause of recurrent chest pain in an adult woman: a case of recurrent stress-induced (Takotsubo) cardiomyopathy

Abstract: SUMMARYRecurrent Takotsubo cardiomyopathy is a relatively uncommon condition seen in patients with severe physical or emotional stress. We report a case of a 51-year-old woman who had recurrent Takotsubo cardiomyopathy with involvement of apical left ventricular (LV) segments, induced by intense emotional stress. On two occasions she presented with symptoms of acute coronary syndrome accompanied by LV regional wall motion abnormalities without a culprit coronary stenosis, and exhibited complete resolution of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Recurrent TCM is known and well described [ 29 - 30 ] and has been estimated to occur rarely with an annual rate of 1.5 - 2.9% [ 11 ] or 1.8% per patient-year [ 14 ]. It is often linked to variable conditions with most common culprits involving excessive emotional or physical stress and seizures [ 31 ], while its prevalence in patients with neurologic and psychiatric diseases is as high as 50%. On review of the literature, we found two cases of recurrent TCM during COPD exacerbations and status asthmaticus, respectively; these cases were again associated with excess adrenergic agonistic-agonist inhalation [ 26 - 27 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent TCM is known and well described [ 29 - 30 ] and has been estimated to occur rarely with an annual rate of 1.5 - 2.9% [ 11 ] or 1.8% per patient-year [ 14 ]. It is often linked to variable conditions with most common culprits involving excessive emotional or physical stress and seizures [ 31 ], while its prevalence in patients with neurologic and psychiatric diseases is as high as 50%. On review of the literature, we found two cases of recurrent TCM during COPD exacerbations and status asthmaticus, respectively; these cases were again associated with excess adrenergic agonistic-agonist inhalation [ 26 - 27 , 32 ].…”
Section: Discussionmentioning
confidence: 99%